The political initiative of Taiwan's education for sustainable development: Looking through the lens of Chinese legalism. Issue 7 (November 2021) - Huang, Ying-Syuan; Asghar, Anila
This article examines the development of Taiwan's Environmental Education Act and how Education for Sustainable Development was mainstreamed into the national policy framework within the country. The goal is to understand the policy tools and governing strategies that were used by the Taiwan government to develop and implement a nationwide environmental education policy for integrating environmental sustainability into all areas and levels of teaching and learning. Official documents related to national plans for ESD and environmental education policies were analyzed and examined. In particular, Chinese Legalism was used as a lens to interpret the government's philosophy, assumptions, unspoken norms, legislative practices, and deliberate strategies. Several principles and techniques proposed by Chinese Legalists were used to examine the negotiation and formulation of Taiwan's Environmental Education Act. This analysis contributes to our understanding of the ways in which UNESCO's framework of ESD can be transferred into a national policy. A discussion of the Chinese Legalist philosophy also offers a cultural frame of reference to think about ESD politics and governance in other East Asian contexts.